ANALISIS KETIDAKSETARAAN GENDER PADA PEREMPUAN DALAM SERIES GADIS KRETEK (2023) - Maharani Harris, Marsya; Nur Suryanto Gono, Joyo; Naryoso, Agus (Interaksi Online, 2024)
Gender inequality between men and women still occurs frequently across various aspects such as social, political, economic, cultural, and industrial spheres, particularly in terms of accessibility. Discrimination against women remains widespread and pervasive in many areas of their lives. The Gadis Kretek series, which premiered on Netflix in November 2023, highlights the importance of understanding gender inequality. Gadis Kretek delivers a social critique on the patriarchal culture and discrimination against women in Indonesia. This study employs a qualitative approach with descriptive methods to analyze and deeply identify the interpretation of gender inequality as experienced by women in the series Gadis Kretek, using hermeneutic analysis. The study draws upon organizational communication theory, standpoint theory, and liberal feminism. Data collection techniques include document observation. The findings reveal discrimination in various aspects of women's lives in the 1960s, particularly in the kretek industry. The main character, Dasiyah, faces obstacles when attempting to continue her family’s business but is not given the same opportunities as men. This inequality is evident in entrenched gender stereotypes and limited access to opportunities and resources for women. A grammatical hermeneutic approach uncovers the historical and narrative context, highlighting workplace gender discrimination, where women like Dasiyah must fight against patriarchal culture to pursue their rights and aspirations. Organizational communication theory and standpoint feminism explain how power structures and gender hierarchies influence social and professional interactions in the series' narrative. Ultimately, Gadis Kretek reflects women's ongoing struggle against gender inequality, a theme that persists into the modern era